Pengaruh Progressive Muscle Relaxation Therapy (PMRT) Terhadap Perilaku Kekerasan Pada Pasien Skizofrenia: Penelitian - Cholila Ramadita; Riko Sandra Putra (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Schizophrenia is a serious mental disorder that affects the way people think, feel, and behave, causing sufferers to often lose touch with reality and struggle with daily activities. Without treatment, sufferers are four times more likely to exhibit impulsive and hostile behavior than people without mental disorders. This study aims to determine the effect of Progressive Muscle Relaxation Therapy (PMRT) on violent behavior in schizophrenia patients. The study used a one-group pretest–posttest pre-experimental design with the Wilcoxon test. The population was schizophrenia patients with violent behavior problems in the Inpatient Ward of Ernaldi Bahar Hospital, South Sumatra in 2025 with 30 respondents selected through purposive sampling. The results showed that PMRT had a significant effect on reducing violent behavior (p-value = 0.000). It is recommended that nurses improve services through non-pharmacological therapies, such as PMRT, murottal, classical music, or color therapy, to reduce violent behavior in schizophrenia patients.